Value creation through stakeholder synergy - Tantalo, Caterina; Priem, Richard L. (Strategic Management Journal, 2016)
Our “stakeholder synergy” perspective identifies new value creation opportunities that are especially effective strategically because a single strategic action (1) increases different types of value for two or more essential stakeholder groups simultaneously, and (2) does not reduce the value already received by any other essential stakeholder group. This result is obtainable because multiple potential sources of value creation exist for each essential stakeholder group. Actions that meet these criteria increase the size of the value “pie” available for essential stakeholder groups, and thereby serve to attract exceptional stakeholders and obtain their increasing effort and commitment. The stakeholder synergy perspective extends stakeholder theory further into the strategy realm, and offers insights for realizing broader value creation that is more likely to produce sustainable competitive advantage . Copyright © 2014 John Wiley & Sons, Ltd.